Packaging systems and storage times serve as post-lethality treatments for Listeria monocytogenes on kippered beef steaks - Lobaton-Sulabo, A.; Uppal, K.; Getty, Kelly J. K.; Boyle, Elizabeth A. E.; Harper, N.; Barry, B.; Higgins, James J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Following several outbreaks involving Listeria monocytogenes in ready-to-eat meat and poultry products, the United States Department of Agriculture Food Safety and Inspection Service required that processors of these products implement post-processing intervention strategies for controlling L. monocytogenes. The USDA defines a postlethality treatment as a process that reduces L. monocytogenes by at least 1 log. Research has shown that packaging can generate a 1 log L. monocytogenes reduction following 1 or more weeks of storage at room temperature. The objective of our study was to determine the effect of packaging system and storage time on reducing L. monocytogenes in shelf-stable kippered beef steak.
Keywords: Beef; Listeria monocytogenes; Steaks; Heat seal; Nitrogen; Vacuum package